Killer whales differentiating in geographic sympatry facilitated by divergent behavioural traditions - Rus Hoelzel; Andre Moura (2016)
Foote and Morin (2016) reanalyse data published in our recent RADseq studies (Moura et al., 2014a, 2015) to address questions about the likelihood of differentiation in sympatry among killer whale populations in the North Pacific. However, they describe a demic version of sympatric differentiation, requiring reproductive isolation to evolve by ‘ecologically driven disruptive selection’ from a background of panmixia. As they point out, questions have been raised about the potential for maintaining linkage between loci associated with ecotype and reproductive isolation, though there are some convincing putative examples of sympatric speciation by this mechanism (for example, Gavrilets et al., 2007). However, we emphasise the potential role of spatial/temporal segregation in the process, as have various authors (for example, Mallet et al., 2009). We have consistently described a process for killer whales whereby the ‘social facilitation of prey location and capture’ (Hoelzel et al., 2007) leads resource specialists to differential spatial and temporal habitat use, even while occupying overlapping geographic ranges, and suggested that this promotes assortative mating and differentiation by both genetic drift and selection (for example, Hoelzel et al., 2007; Moura et al., 2014a, 2015).